2001
DOI: 10.1176/appi.ps.52.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Use of Visual Evoked-Potential Studies and EEG Data to Classify Aggressive, Explosive Behavior of Youths

Abstract: The use of visual evoked-potential studies helped us classify a large subset of youths who exhibited out-of-control explosive behaviors. The findings suggest that a subgroup of individuals exhibiting explosive behaviors may have a predisposition for violent or explosive behavior that is an innate characteristic of their central nervous system. An understanding of the etiology of explosive behaviors permits the use of more appropriate intervention and treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…It was found that the amplitudes of components N1 and Р2 of auditory EPs in healthy subjects negatively correlated with the level of psychoticism [187] and a number of the indices of aggressiveness [188]. At the same time, among teenagers with psychotic deviations, individuals inclined to impulse aggressive behavior demonstrated a higher amplitude of the Р1 component when light flashes and reversion of images were used as the stimuli [189]. Examination of healthy young subjects (students) gave somewhat different results [190].…”
Section: Correlation Of the Characteristics Of Eeg Eps With Peculiarimentioning
confidence: 99%
“…It was found that the amplitudes of components N1 and Р2 of auditory EPs in healthy subjects negatively correlated with the level of psychoticism [187] and a number of the indices of aggressiveness [188]. At the same time, among teenagers with psychotic deviations, individuals inclined to impulse aggressive behavior demonstrated a higher amplitude of the Р1 component when light flashes and reversion of images were used as the stimuli [189]. Examination of healthy young subjects (students) gave somewhat different results [190].…”
Section: Correlation Of the Characteristics Of Eeg Eps With Peculiarimentioning
confidence: 99%
“…Logistic regression analysis indicated that explosive individuals were significantly more likely (p < .0001) to produce high amplitude pattern reversal VEP P100 wave forms recorded at the O1 and O2 electrode sites (Bars, Heyrend, Simpson & Munger, 2001). This one variable accounted for 46% of the explosive individuals.…”
Section: Resultsmentioning
confidence: 96%
“…In another study, adolescent patients who exhibited explosive behaviours (out-of-control anger, out-of-control aggression, verbal or physical attacks on another individuals etc.) were significantly more likely to produce high-amplitude P100 wave forms in response to visual stimuli than patients who did not exhibit these behaviours (Bars et al, 2001).…”
Section: Introductionmentioning
confidence: 89%